Systemic corruption in Brazil: an autopsy of the Odebrecht case - Pohlmann, Markus; Valarini, Elizângela; Trombini, Maria Eugenia; Jorge, Mario (Journal of Self-Regulation and Regulation, 2019)
Brazil has a myriad of corruption scandals in its recent history. Nonetheless, research on the organizational level of corruption is underdeveloped. The paradigm of individual deviance related to wealth grabs hardly applies to the ‘active corruption’ of the bribe giver, as seen in recent cases exposed by Operation Carwash. The holding Odebrecht S.A is at the heart of these scandals. In these cases of bribery, most of the bribe givers are high-ranking, well-educated, and well-paid managers. They are highly connected with public agents and their actions are in line with the company’s goals. We perform an autopsy of the Odebrecht Case and briefly outline what mechanisms and factors on corporate level bolstered a pattern of endemic systemic corruption in the construction sector in Brazil. Our purpose is to contribute to the bigger discussion of corporate crime without overlooking criminological and polity’s perspective but providing an approach from the sociology of organizations. We analyze strengths and weaknesses of regulative insti tuti ons and the environmental conditi ons under which the Brazilian constructi on company-operated and interacted both with its competitors and with public institutions. Based on the judicial documents about Odebrecht and its employees, we reconstruct the factors and mechanisms that are central to organizati onal deviance and provide an overview of the consequences for the company.
Gesehen am 07.07.2020
Keywords: Odebrecht Group; Brasilien; Korruption; Wirtschaftskriminalität